In Vitro Evaluation of Ethanolic Extracts of Ageratum conyzoides and Artemisia absinthium against Cattle Tick, Rhipicephalus microplus - S. Parveen; R. Godara; R. Katoch; A. Yadav; P. K. Verma; M. Katoch; N. K. Singh (The Scientific World Journal)
In vitro efficacy of ethanolic extracts obtained from the aerial parts of Ageratum conyzoides and Artemisia absinthium was assessed on Rhipicephalus microplus using adult immersion test (AIT). Five concentrations of the extract (1.25%, 2.5%, 5%, 10%, and 20%) with three replications for each concentration were used in the bioassay. In AIT, the maximum mortality was recorded as 40% and 66.7% at 20% concentration for A. conyzoides and A. absinthium, respectively. Acaricidal activity was found to be higher in the extract of A. absinthium with LC50 and LC95 values of 11.2% and 61.7%, respectively. Egg mass weight of the live ticks treated with different concentrations of the extracts was significantly (P<0.05) lower than that of control ticks; consequently, the reproductive index and oviposition values of the treated ticks were reduced significantly (P<0.05). The A. conyzoides inhibited 90% hatching of eggs at the 20% concentration, whereas A. absinthium showed 100% inhibition at 5%, 10%, and 20% concentrations. The results show that A. absinthium has better acaricidal properties than A. conyzoides and could be useful in controlling R. microplus.